(3GdTaGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3afbhd Ef GdYdhe GdadSajI ceG bO GTjQ Edjg ai ehGVY CNQi s
(3BNQgG (B:s
(3heLehYgeG GdYOGdi hgj NGQLI Yf GdaVjdI GdfXQjI hef GLJeYJ dg eYgG GdMceI GdfXQjI abO SYO s
(3Hg fXGe GdJYbjHIs
(3ai Chdg agQSJs
(3gPG GdcJGH jMJhi Ydi GdLedI GdQGHYI ai GdEdgjGJ s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs